2013
DOI: 10.7860/jcdr/2013/5348.2970
|View full text |Cite
|
Sign up to set email alerts
|

To Study the Incidence of Heterotopic Ossification After Anterior Cruciate Ligament Reconstruction

Abstract: Introduction: Previous studies have enumerated the advantages of an arthroscopic Anterior Cruciate Ligament (ACL) reconstruction with the use of a Bone Patellar Tendon Bone (BPTB) graft. Complications are extremely rare in such surgeries and one such known complication, which is an extra-articular heterotophic ossification at the femoral tunnel site, is rarely seen only in few patients. Aim:To evaluate the incidence of heterotrophic ossifications at the femoral tunnel site and the efficacy of the preventive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
(16 reference statements)
0
8
0
1
Order By: Relevance
“…After HO excision and a 3-month course of postoperative indomethacin, no recurrence was found at minimum 6-month follow-up. A similar series was published by Bhandary et al 12 in 6 patients, although management was not described. Two studies described HO after multiligamentous knee reconstruction.…”
Section: Resultsmentioning
confidence: 67%
“…After HO excision and a 3-month course of postoperative indomethacin, no recurrence was found at minimum 6-month follow-up. A similar series was published by Bhandary et al 12 in 6 patients, although management was not described. Two studies described HO after multiligamentous knee reconstruction.…”
Section: Resultsmentioning
confidence: 67%
“…X-ray of a patient showing heterotrophic calcification and patellar tendon ossification is shown in Figure 2. The incidence of heterotopic calcification reported in the literature was 1.54%–2.58% and inadvertently scattered bone debris in the operative field was described as the most important cause for it 42. Patellar tendon ossification after ACL reconstruction is an extremely rare complication, and till now only three cases have been reported in literature 434445…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of heterotrophic ossification after ACL reconstruction with BPTB graft vary from 1.54%-2.58%. 21 Mohamed A et al 22 observed that incidence of bone debris after ACL reconstruction surgery was 15% if thorough debridement was done and 65% if no specific debridement protocol was followed. 22 Treatment of patellar tendon ossification is still not well established.…”
Section: Discussionmentioning
confidence: 99%